2019
DOI: 10.11609/jott.5116.11.12.14503-14510
|View full text |Cite
|
Sign up to set email alerts
|

Brief insight into the behavior, activity, and interspecific interactions of urban Trimeresurus (Cryptelytrops) albolabris (Reptilia: Squamata: Viperidae) vipers in Bangkok, Thailand

Abstract: Green Pit Vipers are a widely distributed, diverse group of snakes which occur across a variety of habitats.  Little is known about their natural history in anthropogenically modified environments, and no ecological work has investigated their persistence in cities.  We non-invasively photo-monitored White-lipped Green Pit Vipers Trimeresurus (Cryptelytrops) albolabris in the metropolis of Bangkok, Thailand (n = 4 individuals, mean = 2,658 minutes per individual).  Subsequently, we preliminarily characterize u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Temporal analysis suggested detections with the manual review method should follow previous studies of green pit viper activity patterns (Strine et al 2018, Barnes and Knierim 2019), with behavior events observed primarily at night, early morning, and close to sunset. Overlap between review methods was low (<0.5), but MotionMeerkat observations were spread broad enough temporally to recognize potential presence of behavior events.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Temporal analysis suggested detections with the manual review method should follow previous studies of green pit viper activity patterns (Strine et al 2018, Barnes and Knierim 2019), with behavior events observed primarily at night, early morning, and close to sunset. Overlap between review methods was low (<0.5), but MotionMeerkat observations were spread broad enough temporally to recognize potential presence of behavior events.…”
Section: Discussionmentioning
confidence: 98%
“…Behavior events defined our big‐eyed pit viper ethogram, which is simply a set of terms and descriptions of the behaviors of an animal (Lehner 1987). We classified time‐lapse images (Bushnell cameras) and videos (Brinno cameras) and continuous feed video recordings with a big‐eyed pit viper into one of 4 primary behavior events (following Barnes 2017, Barnes and Knierim 2019): chemosensory probe (probe), strike, mouth gape (gape), and headbob. Behavioral events are relatively instantaneous behaviors (Martin and Bateson 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations